2021
DOI: 10.1186/s41182-021-00307-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the role of digital health technologies in the case detection, management, and treatment outcomes of neglected tropical diseases: a scoping review

Abstract: Background Neglected tropical diseases (NTDs) are a diverse group of communicable diseases that principally impact the world’s poorest people. The use of digital health technologies is an emerging and promising way to improve disease prevention, diagnosis, case detection, treatment delivery, and patient follow-up and facilitating health facility appointments thereby improving health outcomes. While the growing implementation of digital health technologies is evident, there is a lack of comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
0
11
0
2
Order By: Relevance
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed 31 articles that report the burden of prioritized NTDs in Ethiopia (3, 9, 26-35, 11, 36-45, 19, 46, 20-25). Most were systematic reviews and metaanalyses on trachoma (19), leishmaniasis (20)(21)(22)(23)(24), soil transmitted helminthiasis (STH) (25)(26)(27)(28)(29), schistosomiasis (29)(30)(31)(32), scabies (33); LF and podoconiosis (34)(35)(36)(37), review on onchocerciasis (39), and historical review of NTDs in Ethiopia (1941-2019) (38). Trachoma, podoconiosis and leishmaniasis are three common NTDs in Ethiopia (3,11).…”
Section: Evidence On Burden Of Ntds In Ethiopiamentioning
confidence: 99%
“…Podoconiosis and trachoma are also common in Ethiopia, mainly in Amhara, Oromia and Southern Nation, Nationalities and Peoples (SNNP) regions (44). NTD distributions at country level have been mapped, and endemic areas identi ed and prioritized (35,45,46).…”
Section: Evidence On Burden Of Ntds In Ethiopiamentioning
confidence: 99%
“…Previous works comparing electronic data collection to paper-based data collection for NTDs have shown that data collected through electronic sources were less expensive, more efficient, and produced higher quality data with fewer errors [10,11]. However, there are few studies describing digital health technologies in surveillance, management, and treatment of NTDSs [12]. Although some studies reported on enhancements of the surveillance and management of NTDs, they were limited to the description of specific tools used for those processes [12][13][14].…”
Section: Public Health Informatics Contextmentioning
confidence: 99%
“…However, there are few studies describing digital health technologies in surveillance, management, and treatment of NTDSs [12]. Although some studies reported on enhancements of the surveillance and management of NTDs, they were limited to the description of specific tools used for those processes [12][13][14].…”
Section: Public Health Informatics Contextmentioning
confidence: 99%